Efektifitas Media Promosi Kesehatan Dalam Penanganan Stunting (Literatur Review) - M. Sahli (Pusat Riset dan Inovasi Nasional, 2021)
Health promotion media is media that can support the success of health promotion efforts. Determining good media is one that suits the characteristics of the target. Handling health problems requires health promotion media as an effort to make it easier for officers to deliver material according to target, place, age and time. The more five senses that utilize the media, the easier it is for the target to receive the counseling material. The method used in this research is a literature review using a library review method, data obtained from articles taken from journal search engines. The results of this research show that variations in the visual media of posters, leaflets and flip sheets will make it easier for the public to receive knowledge from health promotion officers. Keywords: , Stunting.